Antisocial, narcissistic, and borderline personality disorders : a new conceptualization of development, reinforcement, expression, and treatment - Fox, Daniel J., Psychologist (New York, NY : Routledge, 2021)
"This book provides a framework for scholars and clinicians to develop a comprehensive and dynamic understanding of Antisocial, Narcissistic, and Borderline Personality Disorders, by seeing personality as a dual, as opposed to a singular, construct. Converging the two separate research and clinical diagnostic systems into a wholistic model designed to reach reliable and valid diagnostic conclusions, the text examines adaptive and maladaptive personality development and expression, while addressing the interpersonal system that keeps the pathology from extinguishing. Each chapter will discuss core and surface content, origin and symptom manifestation, system and pathology perpetuation, and online behavior expression, concluding with practical guidance on treatment success and effective approaches. Seasoned and tyro researchers and clinicians will be challenged to explore the utility of the alternative model of personality disorders and apply it to further the understanding of these complex, and often destructive, disorders"--
Antisocial Personality Disorder (ASPD) -- Narcissistic Personality Disorder (NPD) -- Borderline Personality Disorder (BPD).
OCLC-licensed vendor bibliographic record.
Keywords: Personality disorders; Antisocial personality disorders; Narcissism; Borderline personality disorder; PSYCHOLOGY / Mental Health